초등학교 영재학급용 교수·학습 자료 개발을 위한 가변칠교판 활용 소재 발굴 - 강민정; 송상헌 (한국초등수학교육학회지, 24(1), 2020)
본 연구는 보통의 초등학생들에게도 익숙한 전통칠교판을 변형하여 만든 가변칠교판을 활용하여 초등학교 영재학급용 교수·학습 자료 개발을 위한 소재 발굴을 목적으로 한다. 가변칠교판은 영재학급 학생들이 수학적 의사소통을 통해 정당화를 수 있다. 다만, 영재학급 학생이라도 초등학교 수준에서는‘기호화’단계를 거치지 않으면 모든 크기의 삼각형, 직사각형을 찾아 정당화(증명)하기에는 어느 정도의 한계가 있다. 따라서 문자와 기호에 대한 탐구 과정이 필요한 학생들에게는 보충 학습 자료와 추가 발문을 제공할 필요가 있다. 초등학교 영재학급용 교수・학습 자료 개발을 위한 가변칠교판이라는 소재는 영재학급 학생들의 수학적 추론능력과 수학적 의사소통능력을 발달시키는데 기여할 수 있을 것으로 기대한다. The purpose of this study is to find new material for developing teaching and learning materials for the gifted class of elementary school students by using the rotatable tangram made by modifying the traditional tangram. Rotatable tangram can be justified by gifted students through mathematical communication. However, even gifted class students have some limitations in finding and justifying triangles and rectangles of all sizes unless they go through the 'symbolization' stage at the elementary school level. Therefore, students who need an inquiry process for letters and symbols need to provide supplementary learning materials and additional questions. It is expected that the material of rotatable tangram for the development of teaching and learning materials for elementary school gifted students will contribute to the development of mathematical reasoning and mathematical communication ability. KCI Citation Count: 0